Fundamental studies of ionic liquid electrolytes aiming at application in Na metal-based batteries - Dias Ferreira, Lais (2021)
In this thesis, the tunability of ionic liquids was explored to design a series of ILs and evaluate the impact of different IL-based electrolytes on metallic Na electrode cells. This was done by performing a comprehensive investigation involving Na+ plating/stripping and electrode surface resistance over time (resting and cycling time). In addition, a novel study of solid-electrolyte interphase (SEI) structure and composition was carried out with 3D OrbitrapTM secondary ion mass spectroscopy (3D OrbiSIMS) in depth profiling mode. The unique sensitivity and mass resolution of the 3D OrbiSIMS, and the use of an Ar cluster primary ion beam as a sputtering and analysis beam allowed us to obtain vast and detailed information relating to the nature and distribution of the SEI-products in the interphase. Consequently, we were able to accurately determine the effects of anion and cation variation on the SEI structure. This allowed us to identify key structural features to design high performing stable electrolytes for use in Na-electrode cells. It was demonstrated that the distribution of SEI-products into an organised structure is critical to achieve a stable SEI. In addition, low overpotential during Na symmetrical cycling, and stabilisation of surface resistance was achieved with the IL that demonstrated the most organised SEI structure. Furthermore, the impact of the commonly used [PF6]-based salt as an additive was also investigated. It was found that the presence of [PF6] additive improves SEI stability and cycling time of symmetrical cells. 3D OrbiSIMS studies of the SEI with the [PF6] additive revealed that the organisation of the structure of the SEI has a greater influence on the improved performance of cells than the presence of fluoride products in the SEI itself.